NUCLEOLI OF DIPLOID CELL STRAINS : Their Normal Ultrastructure and the Effects of Toyocamycin and Actinomycin D - Phillips, Stephanie G. (The Rockefeller University Press, 1971)
Nucleoli of cultured Chinese hamster or mouse cells in early passages had a loosely reticular substructure. Within the reticulum small, irregularly shaped, light fibrillar zones occurred which were contiguous with denser fibrillar zones. These denser zones appeared to be connected in some places to the particulate material which composed the mass of the nucleolus. Generally, electron-transparent spaces separated the particulate zones from the fibrillar areas. Treatment with toyocamycin, an agent which is reported to cause a blockage in the processing of ribosomal RNA, greatly inhibited the accumulation of newly synthesized RNA in the cytoplasm, as monitored by radioautography. Toyocamycin treatment caused the gradual disappearance of the granules from the particulate region of the nucleoli, and resulted ultimately in the nucleoli appearing homogeneously fibrillar. Actinomycin D treatment, which inhibited virtually all RNA synthesis, caused a segregation, and finally a disaggregation, of nucleolar components.